Emergency response applying Geographical Information Technologies to the spread of COVID-19 in Peru - Gonzales Gonzales, Miqueas (2020)
This research aims to develop a didactic proposal for the use of Geographic Information Technologies (TIG), which will allow authorities to access more resources to make better decisions in tasks of monitoring, controlling and responding to the COVID -19 (disease associated with SARS-CoV-2 infection) pandemic. The entire universe of the population in the Peruvian territory was analyzed. Through specialized Geographic Information Systems (GIS) programs designed to show multiple visualizations on a single screen, a complete and attractive view of the data is offered. Results obtained show tables and projections of COVID-19, concluding that it affects more men than women, its mortality rate is 3.82% and the largest number of deaths are older adults, claimed the lives of 193 people and infected 7519 until April 11, 2020. It is planned that the next 12th may, COVID-19 reaches the maximum number of infected